Disability Policies and Management in Bolivia: Changes and Challenges. (June 2022) - García-Domingo, M.; Fuentes, V.; De La Fuente Robles, Y. M.; Muyor, J.
The Plurinational State of Bolivia has experienced significant social changes with a growing commitment toward policies that favor vulnerable populations. Acknowledging movements led by people with disabilities to promote progress in social policies is a crucial task. The public sector has responded to the demands and needs of this population through recognition and promotion of their rights. Nevertheless, to ensure progress, we must support the voices of the stakeholders and promote their participation in identifying the strengths and weaknesses of the system, and the real needs and demands of people with disabilities in Bolivia. To this end, in this study, we gathered statements of key informants, using a focus group technique. The results of the data analysis indicate an increase in social awareness and recognition of the needs of this collective and the importance of their full inclusion in society. However, there is a distortion in the application of certain assistance and inclusion policies in favor of people with disabilities because these policies do not have their intended impact.